System control through the internet and a remote access laboratory implementation - (:unkn) unknown (SPRINGER-VERLAG BERLIN, 2008)
Nowadays, remote access laboratories are getting popular in technical education. This paper illustrates a Remotely Access Control Laboratory (RACL) implementation in which students can make control experiments on a real plant through the Internet. Process Level Trainer is used as a plant, which is a practice environment for the fundamentals of the process control education. A Data Acquisition Card (DAQ Card) installed Computer, as a control unit, is connected to the plant. A pan-tilt movable, CCD, IP Camera is preferred to transmit the look of the plant during the experiment. In order to control the plant through the Internet, special control software is developed using Delphi programming language and web pages including PHP scripts are designed. A Flash object is also developed for displaying the result graphics of experiments online. A user, after login from any computer that has an Internet connection, can easily study basic control algorithms, such as Open Loop, On-Off, PID with changing their parameters as well.
Keywords: web based control; remote laboratory; remote access laboratory; remote access control laboratory